Neutrophil depletion at the early stage of Japanese encephalitis virus infection affects CD8+ T cell infiltration into the mouse brain and causes severe encephalitis - Soni, Rohit; Jena, Prasanjit; Kusuma, B.; Banerjee, Arup (Frontiers in Immunology, 2026)
Neutrophils have been reported to have protective and detrimental functions in viral infections. However, the role of neutrophils remains unexplored in Japanese encephalitis virus (JEV) infection. In this study, we elucidated the dynamics of neutrophils and their influence on immune cell recruitment in subclinical and severe encephalitis in mouse models. Further, we depleted neutrophils from 3–4 week-old C57BL/6 mice using mAb1A8 (anti-Ly6G) antibody and studied their association with inflammation, viral replication, immune cell infiltration and disease outcome. We observed that an increase in JEV replication is associated with increased infiltration of neutrophils in the spleen and brain. Further studies confirmed that depletion of neutrophils at an early stage of JEV infection reduced CD8 abundance in the infected brain and accelerated death in mice. We also observed that inhibition of the CXCL12-CXCR4 signalling axis by antagonist AMD3100 reduced CD8 abundance in the brain and augmented inflammasome activation, leading to fatal encephalitis. Reduced CXCR4 levels in the spleen and blood of CD8+T cells correlated with enhanced Granzyme B level, indicating CD8 cells differentiated more into effector phenotypes in neutrophil-depleted mice. Furthermore, CD8 depletion delayed the death of mice infected with a sublethal strain compared to neutrophil-depleted mice, suggesting that neutrophils play a vital role in the early restriction of viral replication, whereas CD8 is essential later in clearing the virus. Taken together, our study sheds new light on the role of neutrophils in the pathogenic mechanisms of JEV encephalitis and highlights the importance of neutrophils and CD8 cells associated with disease outcomes.